A Fuzzy Probabilistic hybrid approach to evaluate the impact of component outages, demand and generation cost uncertainties in the operation of power systems - Bruno André Gomes (2011)
This paper reviews the concepts and the solution algorithm of the Fuzzy DC OPF problem admitting generation costs and load values modeled by fuzzy numbers and details the integration of this problem in the Monte Carlo simulation model. In this sense, the paper describes an hybrid approach in which generation cost and demand uncertainties are represented by fuzzy numbers and the life cycle of the system components is modeled by probabilistic approaches. On this topic, the paper addresses the sampling procedure, the analysis of sampled states, the convergence testing and the computation of the expected values of the system Power Not Supplied and system risk indices. Finally, the paper includes results based on the IEEE 24 bus/38 branch test system to illustrate the proposed approach.